Multidisciplinary Optimization for Weight Saving in a Variable Tapered Span-Morphing Wing Using Composite Materials—Application to the UAS-S4 - Mohamed Elelwi; Felipe Schiavoni Pinto; Ruxandra Mihaela Botez; Thien-My Dao (Actuators, 2022)
This paper is a follow-up to earlier work on applying multidisciplinary numerical optimization to develop a morphing variable span of a tapered wing (MVSTW) to reduce its weight by using composite materials. This study creates a numerical environment of multidisciplinary optimization by integrating material selection, structural sizing, and topological optimization following aerodynamic optimization results with the aim to assess whether morphing wing optimization is feasible. This sophisticated technology is suggested for developing MVSTWs. As a first step, a problem-specific optimization approach is described for specifying the weight-saving structure of wing components using composite materials. The optimization was performed using several approaches; for example, aerodynamic optimization was performed with CFD and XFLR5 codes, the material selection was conducted using MATLAB code, and sizing and topology optimization was carried out using Altair’s OptiStruct and SolidThinking Inspire solvers. The goal of this research is to achieve the MVSTW’s structural rigidity standards by minimizing wing components’ weight while maximizing stiffness. According to the results of this optimization, the weight of the MVSTW was reduced significantly to 5.5 kg in comparison to the original UAS-S4 wing weight of 6.5kg. The optimization and Finite Element Method results also indicate that the developedmorphing variable span of a tapered wing can complete specified flight missions perfectly and without any mechanical breakdown.